Introduction: groundwater, sustainable livelihoods and equitable growth - Re, V.; Manzione, R. L.; Abiye, T. A.; Mukherji, Aditi; MacDonald, A. (2022)
In many areas of the world, groundwater represents the primary source of water for domestic supply and agriculture, supporting livelihoods and lifting many out of poverty. However, the hidden nature of groundwater often means that its important role both historically and in the present is overlooked, hampering its effective management and putting future supplies at risk. For the benefits of groundwater abstraction to continue to be realized and sustained, the links between groundwater availability and quality, climate change, and groundwater-dependent livelihoods need to be explored and articulated. This becomes even more important with growing climate uncertainty and decreasing water security in some marginal and vulnerable areas, with an increasing threat to livelihoods. This introductory chapter presents the main concepts of this book, introduces the different chapters, and discusses emerging themes. There is compelling evidence that the development of groundwater has profoundly improved many people’s lives and continues to lift people out of poverty today. The examples in this book provide a wide variety of case studies from Asia, Africa, and South America that show how groundwater, often invisibly, improves people’s lives and livelihoods and promotes equitable growth. However, the studies also demonstrate how vulnerable groundwater can be over-used and contaminated, and how ignorance of the nature of groundwater is one of the greatest threats to its sustainable use. It is, therefore, of critical importance to increase investment in characterizing, monitoring, and governing groundwater, to explore links between science, policy, and practice, and to effectively communicate existing knowledge so that groundwater will continue to improve people’s lives for centuries to come.